Increased reproductive outcomes after optimized sperm preparation - Gómez-Elías, Matías D.; Luque, Guillermina M.; Oscoz-Susino, Natalia; Novero, Analía G.; Briski, Olinda; Kásparas, Inés; Steeman, Tomás J.; Stival, Cintia; Lavolpe, Mariano; Julianelli, Vanina; Geller, Marisa; Attie, Martín; et al. (Frontiers in Cell and Developmental Biology, 2025)
A key factor to the success of in vitro fertilization (IVF) is the preparation of human sperm, a critical step that directly impacts the efficacy of the procedure. This proof-of-concept study evaluated the effect of HyperSperm, a novel sperm preparation technique designed to enhance sperm function, on fertilization, embryo development, and pregnancy outcomes in both a mouse model and a first-in-human trial following IVF. In mice, HyperSperm treatment significantly increased hyperactivated motility (p < 0.05), leading to improved fertilization and blastocyst development (p < 0.05), as well as higher implantation rates (p < 0.05) and larger litter sizes (p < 0.05). Offspring displayed normal growth and fertility. In human sperm samples from normozoospermic men, HyperSperm exhibited a high safety profile, with motility, acrosome reaction, viability, and DNA fragmentation comparable to controls. A first-in-human, prospective, single-center, split-oocyte study in 10 couples undergoing IVF with donated oocytes demonstrated similar fertilization rates between HyperSperm and control groups (p = 0.425), but significantly higher usable blastocyst rates in the HyperSperm arm (43.8% vs. 67.9%, p = 0.0122). Morphokinetic parameters were comparable between groups. These results suggest that HyperSperm enhances sperm hyperactivation, a hallmark of capacitation, leading to improved embryo development in both mice and humans. This technique represents a promising approach to optimizing sperm preparation in assisted reproduction, warranting further clinical investigation.